-3x+3=4x+10

Simple and best practice solution for -3x+3=4x+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+3=4x+10 equation:


Simplifying
-3x + 3 = 4x + 10

Reorder the terms:
3 + -3x = 4x + 10

Reorder the terms:
3 + -3x = 10 + 4x

Solving
3 + -3x = 10 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
3 + -3x + -4x = 10 + 4x + -4x

Combine like terms: -3x + -4x = -7x
3 + -7x = 10 + 4x + -4x

Combine like terms: 4x + -4x = 0
3 + -7x = 10 + 0
3 + -7x = 10

Add '-3' to each side of the equation.
3 + -3 + -7x = 10 + -3

Combine like terms: 3 + -3 = 0
0 + -7x = 10 + -3
-7x = 10 + -3

Combine like terms: 10 + -3 = 7
-7x = 7

Divide each side by '-7'.
x = -1

Simplifying
x = -1

See similar equations:

| y=xsin^2*(2x) | | (x^3+y^4)dx-8xy^3*dy=0 | | -3(x+4)+4x=-24 | | 2(x+3)+7=8x-8 | | y=5/4x-7 | | 2s(t+-7)+-6t(s+3)= | | (4x+8)(8x-4)=0 | | 3x+9=8x+3 | | 5g-2+4g+20=180 | | (7x-4)=(x+32) | | y=-7x+b | | -3(x+4)+4x=-2 | | x/3+7=2 | | 4x+14=6/5+7 | | 74-22=13Y | | 7.92y=2.2x | | .10(x)+.25(y)=12.55 | | 39.95-0.49x=75 | | 8(j-3)=4j+9j+-14 | | 125+55x=400 | | X^2+y^2+2x+4y=20 | | 3y=8x | | -3(2x-4)+8x=20 | | 15y=5x | | y^2-8y+0=0 | | 6(7-10x)+3(3-15x)=336 | | 25-4x=97 | | 10(x)+25(y)=12.55 | | 7-1.5ln*15= | | 5(y+2)-3=y-5+y | | 8C^4/11C^4 | | 3x+2x-1=69 |

Equations solver categories